Pengembangan Instrumen Penilaian Kepuasan Pasien terhadap Pelayanan Kefarmasian di Rumah Sakit - Dedy Almasdy; Yulihasri Yulihasri; Dila Deria Putri (Jurnal Sains Farmasi & Klinis, 2015)
Instrument to assessing patient satisfaction to hospital pharmacy services has developed. The instrument consists of two dimensions which are friendly explanation and managing theraphy. The result of instrument developing are a instrument which have fair to good of the level of agreement (ĸ = 0.53), fair to good validity (r > 0.632) and good reliability (cronbach alpha = 0.97).